Heterosis under aerobic condition in hybrid Rice - K Amudha, K. Thiyagarajan, S. Robin, Silvas Jeba Kumar Prince, R. Poornima and K.K. Suji (Electronic Journal of Plant Breeding, 2010)
An experiment was undertaken to identify heterotic rice hybrids for aerobic condition based on physiological and rootcharacters associated with water stress tolerance in rice. Panicle harvest index, a substitute for spikelet fertility is used as asecondary trait in the selection of drought tolerant genotypes. Deep roots are required to explore the soil profile foreffectively absorbing water at deeper layers. A cultivar which partitions more of its dry weight in root can explore more soilvolume for extracting water and thus can effectively sustain drought. Four hybrids viz., IR 68885A / IR 73718-3-1-3-3, IR67684A / CT-6510-24-1- 2, IR 70369A / IR 73718-3-1-3-3 and IR 70372A/ PSBRC 80 exhibited heterotic vigour for yieldand maximum number of yield components and showed better adaptability to aerobic conditions. These hybrids can becommercially exploited under aerobic condition.